(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Hospitals and industrial settings both use the chemical molecule formaldehyde. The pineal gland releases the endogenous hormone melatonin. There are antioxidant properties of melatonin. Aim of Study: This study sought to identify the aberrant histological alterations in adult albino rats’ testicles brought on by formaldehyde as well as any potential preventive benefits of taking a melatonin medication in addition to formaldehyde. Material and Methods: Three sets of 30 mature rats weighing between 190 and 210 g were created; Group I (control): For a month, rats in this group received intraperitoneal injections of 5% ethanol once every 2 days. Group II (Group treated with formaldehyde): For a month, rats received intraperitoneal injections of formaldehyde at a dose of 10 mg-kg BW 1 time every other day. The last group, which was treated with both melatonin and formaldehyde, involved injecting rats intraperitoneally with 10 mg-kg BW of formaldehyde and 25 mg/kg BW of melatonin an hour later. For a month, both medications were administered once every other day. The testes were removed from the rats, and prepared for light microscopy using hematoxylin and eosin. Results: Rats given formaldehyde showed tubular degeneration, thicker tunica albuginea, loss of normal tubule architecture, degenerated nuclei with thickened and indented nuclear envelope, and a karyolitic nucleus. Rats given both formaldehyde and melatonin treatment showed a clear improvement in the prior changes. Conclusion: It is necessary to provide melatonin to employees in the anatomy department and food industries because it was found that formaldehyde caused histological changes in the testis. These changes were improved by the use of melatonin. However, more research is needed to determine the appropriate dosage and administration method for humans.